Differential equations - Bautista, Lincoln; Bernardo, Jr., Servando;Gregorio, Floreben V.;Merza, Melinda V.;Nobles, Bernadeth G.;Mateo, Rolando A.;Mendoza, Rodolfo V.;Ramos, Elizabeth B. ([Place of publication not identifed] : [publisher not identified], 1999)
It is the fervent hope and ardent desire of the authors that this book would be very instrumental in enhancing and optimizing the knowledge of the students in the field of mathematics.
Chapter 1. Basic concepts -- Chapter 2. Separation of variables -- Chapter 3. Homogeneous equations -- Chapter 4. Exact equations -- Chapter 5. Linear equations -- Chapter 6. Bernoulli's equations -- Chapter 7. Equations reducible to homogeneous form -- Chapter 8. Determination of integrating factor -- Chapter 9. Linear equations with constant coefficients -- Chapter 10. Nonhomogeneous linear differential equations -- Chapter 11. Inverse operator -- Chapter 12. Elementary applications -- Chapter 13. Laplace transforms -- Chapter 14. Inverse laplace transforms.
Includes bibliographical references.
Keywords: DIFFERENTIAL EQUATIONS -- MATHEMATICS